Impact on Transformational, Professional Leaders and Work Discipline on Lecturer Performance Through Organizational Commitment of Private University at LLDIKTI Region IX - Hatta, Moh (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
The lecturers' effectiveness is a key indicator of how higher education is improving. The university will do better the more well its lecturers perform. Performance results from lecturers carrying out their assigned tasks, in this case, implementing the higher education tri-dharma, which consists of teaching, research, and civil service. Achieving both the quantity and quality of higher education's tridharma implementation requires several criteria that impact both internal and external considerations. This research examines how organizational commitment in private higher education institutions in LLDIKTI Region IX affects lecturer performance regarding professionalism. Explanatory research using a quantitative approach directed by questionnaires is employed in the research design. Primary data was analyzed descriptively, and Structural Equation Modeling (SEM) was used. Based on research results, professionalism can improve lecturer performance. In this regard, it was found that professionalism can most influence lecturer performance. In particular, professionalism in social competence is reflected in the ability to express opinions. The main thing that can improve lecturer performance is having social competence that can build good and stable collaboration with other lecturers, education staff, students, and the community to support education.